2007
DOI: 10.1002/smll.200600511
|View full text |Cite
|
Sign up to set email alerts
|

Proteins and Carbon Nanotubes: Close Encounter in Water

Abstract: The interactions between biological substances and carbon nanotubes (CNTs) and their effect on the nanotubes are of significant importance in this emerging era of nanobiotechnology. Consequently, highly stable dispersions of debundled CNTs in aqueous solution are an important prerequisite for their applications and for the development of nanotube-based molecular electronic and nanobiomedical devices. Here, we report that proteins can work as tools to this end if their primary structure and the pH value of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
162
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(169 citation statements)
references
References 31 publications
7
162
0
Order By: Relevance
“…The analysis shows that LSZ-SWNT dispersions clear approximately 55% of turbidity (optical density at 450 nm) within 5 min compared to 60% for the LSZ dispersion. The decrease in optical density due to cellular lysis confirms that secondary structure of LSZ in LSZ-SWNT conjugate is well preserved 16 as required for enzyme activity. In contrast, the DNA-SWNT dispersions showed no reduction in turbidity, suggesting that the SWNTs did not contribute to cell lysis.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…The analysis shows that LSZ-SWNT dispersions clear approximately 55% of turbidity (optical density at 450 nm) within 5 min compared to 60% for the LSZ dispersion. The decrease in optical density due to cellular lysis confirms that secondary structure of LSZ in LSZ-SWNT conjugate is well preserved 16 as required for enzyme activity. In contrast, the DNA-SWNT dispersions showed no reduction in turbidity, suggesting that the SWNTs did not contribute to cell lysis.…”
mentioning
confidence: 62%
“…15 Similarly, favorable intermolecular interactions enable dispersion of individual and small bundles of SWNTs in proteins such as LSZ. 11,16,17 In this research, the strong Coulombic interactions between DNA and LSZ were exploited in the layer-by-layer (LBL) assembly 18-20 of DNA-SWNT and LSZ-SWNT dispersions.The enzymatic activity of LSZ in the SWNT dispersions was determined by measuring the rate of lysis of Grampositive Micrococcus lysodeikticus intact cells (Figure 1). The responses from the turbidimetric assay were modeled with first-order kinetics typically used to quantify exponential death of microorganisms (Figure 1b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…46 Stable dispersions are the result of electrostatic or steric repulsion provided by the coating molecules as well as favorable van der Waals, hydrophobic, and π-stacking interactions at the SWCNT interface dominating over the strong van der Waals attractive forces between the carbon nanotubes. 30,47 Figure 1. Overview of approaches for noncovalent protein (blue) conjugation to a SWCNT (black): (a) nonspecific physical adsorption of a protein to a SWCNT, (b) hybrid conjugation through covalent attachment to noncovalent wrappings (magenta), and (c) protein binding to heterobifunctional linker molecules (magenta) adsorbed onto SWCNTs.…”
Section: Nonspecific Protein and Peptide Adsorptionmentioning
confidence: 99%
“…Bundle-free or isolated SWCNTs typically exhibit sharp peaks in the visible and near-infrared regions of the optical absorbance spectra due to the van Hove transitions of metallic and semiconducting SWCNTs. 30 Broad, weak absorbance peaks often indicate the presence of aggregated SWCNTs, since the van der Waals interactions between stacked tubes disturb the electronic structure of SWCNTs. 1 Several studies have identified a protein:SWCNT threshold (e.g., 5:1 for BSA:SWCNT) below which a high yield but poor dispersion quality is obtained and above which a higher dispersion, but smaller yield, is obtained.…”
Section: Nonspecific Protein and Peptide Adsorptionmentioning
confidence: 99%